Farmer Perceptions Related to Potato Production and Late Blight Management in Two Communities in the Peruvian Andes - Pérez, W.; Forbes, G.; Arias, R.; Pradel, W.; Kawarazuka, Nozomi; Andrade-Piedra, J.L. (Frontiers Media, 2022)
Potato late blight (LB), caused by the oomycete, Phytophthora infestans, continues to be a major constraint of potato in the Andean region and worldwide. Farmers perception regarding potato production with particular emphasis on management practices for LB was surveyed in two communities in the Peruvian highlands using a questionnaire with 25 questions, many with multiple choice questions. In the village of Paucartambo, 84 women and 485 men of different ages participated in the survey, while in the village of Ulcumayo, there were 146 women and 396 men, also of different ages. Overall, responses were similar between the two locations, with some small but significant differences. In general, there was a very clear association between age and education, with only young men and women having secondary education. Respondents in both locations overwhelmingly chose LB as the main constraint to production and cited either personal experience or agrochemical vendors as the primary sources of information about disease management. Many cultivars (25+) are grown in both locations, with the two most important cultivars, Yungay and Huayro, being common in both locations while others differed. There was evidence of confusion around the concept of host plant resistance, as certain cultivars were cited as both relatively resistant and susceptible. Many trade names of fungicides were recalled by respondents, but most were relatively old products. Correspondence analysis indicated gender effects on LB management practices and information sources in both locations that could be taken into consideration to refine future interventions for research and capacity building, such as offering refresher training courses for extension educators, including female extension workers, to help farmers understand basic concepts to manage host resistance and fungicides properly, and improve access to resistant varieties and effective fungicides.